Survey of VPU olympiad 2011 for young mathematicians - Jakaitytė, Eglė; Kaučikas, Algirdas; Mazėtis, Edmundas (Lietuvos matematikos rinkinys, 2011)
The texts and solutions of the VPU young mathematicians olympiad – 2011 are presented.